Heterogeneous consumers, segmented asset markets, and the real effects of monetary policy - Zeno Enders (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper proposes a novel mechanism by which changes in the distribution of money holdings have real effects. Specifically, I develop a flexible-price model of segmented asset markets that generates real aggregate effects of monetary policy through the dependence of optimal markups on the heterogeneity of money holdings. Because varieties of consumption bundles are purchased sequentially, newly injected money disseminates slowly throughout the economy via second-round effects.
Keywords: E31; 330